Determinación de la demanda bioquímica de oxígeno (DBO5) del Río Jubones. En el sector Quera provincia de El Oro - Ordóñez Jumbo, Sonia M. (2006)
The Biochemical demand of Oxygen (DBO) she helps to determine the present quanty of organic residue in the water, because it measures the quantity of oxygen that the microorganisms need for to consume this residue.